Heavy Ion Reactions Proceeding Via 221*Ac Compound Nuclei - Gough, Richard Arthur (My University, 1970)
A high speed recoil transport system is developed making possible the simultaneous study of many decay products of the compound nucleus 221*Ac. Oeterminati ons of the efficiency properties of the transport system, essential for absolute cross section measurements , are discussed in detail.
A study of angular momentum effects is made possibly by synthesis of 221*Ac using three heavy ion reactions. Absolute cross sections for (HI,xn) and (HI,pxn) reaction products are determined relative to established cross sections for production of 150Dy. Relative cross sections for francium production are also determined.
A sophisticated statistical model calculation is adapted to provide a framework for interpretation of the results. Some insight is gained into the roles played by basic physical concepts in the systematic of compound nucleus decay in this mass region
Keywords: high speed recoil transport system, decay, 221*Ac, angular momentum, heavy ion reactions